Solar Jets: SDO and IRIS Observations in the Perspective of New MHD Simulations - Schmieder, Brigitte (Frontiers in Astronomy and Space Sciences, 2022)
Solar jets are observed as collimated plasma beams over a large range of temperatures and wavelengths. They have been observed in H$α$ and optical lines for more than 50 years and called surges. The term "jet" comes from X-ray observations after the launch of the Yohkoh satellite in 1991. They are the means of transporting energy through the heliosphere and participate to the corona heating and the acceleration of solar wind. Several characteristics have been derived about their velocities, their rates of occurrence, and their relationship with CMEs. However, the initiation mechanism of jets, e.g. emerging flux, flux cancellation, or twist, is still debated. In the last decade coordinated observations of the Interface Region Imaging Spectrograph (IRIS) with the instruments on board the Solar Dynamic Observatory (SDO) allow to make a step forward for understanding the trigger of jets and the relationship between hot jets and cool surges. We observe at the same time the development of 2D and 3D MHD numerical simulations to interpret the results. This paper summarizes recent studies of jets showing the loci of magnetic reconnection in null points or in bald patch regions forming a current sheet. In the pre-jet phase a twist is frequently detected by the existence of a mini filament close to the dome of emerging flux. The twist can also be transferred to the jet from a flux rope in the vicinity of the reconnection by slippage of the polarities. Bidirectional flows are detected at the reconnection sites. We show the role of magnetic currents detected in the footprints of flux rope and quasi-separatrix layers for initiating the jets. We select a few studies and show that with the same observations, different interpretations are possible based on different approaches {\it e.g.} non linear force free field extrapolation or 3D MHD simulation.